Influence of Leadership Training Level III, Creativity and Commitment to Performance of Employees Duties of Health Ministry of The Republic of Indonesia - Haslinda Daulay; Ma'ruf Akbar; Mansyur Ramly (IJHCM (International Journal of Human Capital Management), 2018)
The purpose of this study was to study the effect of level III leadership training, creativity and task commitment on employee performance. The research process was carried out at the Ministry of Health of the Republic of Indonesia using a case study method. The study sample was 168 employees of the Ministry of Health of the Republic of Indonesia who were selected by simple random sampling from 289 populations. The findings are: (1) there is a positive direct effect of level III leadership training on employee performance, (2) there is a positive direct effect of creativity on employee performance, (3) there is a positive direct influence on task commitment to employee performance, (4) direct influence positive level III leadership training on creativity, (5) there is a positive direct influence on task commitment to creativity. Referring to these findings, researchers can conclude that employee performance is positively influenced by level III leadership training, creativity and task commitment. Therefore, to maintain employee performance, organizations must implement level III leadership training, creativity and task commitment. Finally, it was concluded that level III leadership training, creativity and task commitment must be considered in producing employee performance.